2023
DOI: 10.1002/prot.26635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ion type and concentration on the structure and aggregation of the amyloid peptide Aβ16−22$$ {\boldsymbol{\beta}}_{16-22} $$

Eva Smorodina,
Batuhan Kav,
Hebah Fatafta
et al.

Abstract: Among the various factors controlling the amyloid aggregation process, the influences of ions on the aggregation rate and the resulting structures are important aspects to consider, which can be studied by molecular simulations. There is a wide variety of protein force fields and ion models, raising the question of which model to use in such studies. To address this question, we perform molecular dynamics simulations of Aβ16–22, a fragment of the Alzheimer's amyloid β peptide, using different protein force fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Given the abundance of Zn 2+ in Aβ aggregated structures, our study highlights the role of Zn 2+ playing in the assembled structure of Aβ 16–22 and gives a clue on modulating the assemble process by the addition of Zn 2+ ions. We note that other metal ions have also shown a similar effect for the disruption of the salt bridge. , Using the same force field CHARMM36m, Strodel et al found that Ca 2+ can bind to Glu22 of Aβ 16–22 and inhibit peptide aggregation by disrupting the Lys16-Glu22 salt bridge . Another study on the full-length Aβ showed that Na + aggregate near Glu22 and Asp23, thus screening the electrostatic interaction between Glu22/Asp23 and Lys28 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Given the abundance of Zn 2+ in Aβ aggregated structures, our study highlights the role of Zn 2+ playing in the assembled structure of Aβ 16–22 and gives a clue on modulating the assemble process by the addition of Zn 2+ ions. We note that other metal ions have also shown a similar effect for the disruption of the salt bridge. , Using the same force field CHARMM36m, Strodel et al found that Ca 2+ can bind to Glu22 of Aβ 16–22 and inhibit peptide aggregation by disrupting the Lys16-Glu22 salt bridge . Another study on the full-length Aβ showed that Na + aggregate near Glu22 and Asp23, thus screening the electrostatic interaction between Glu22/Asp23 and Lys28 .…”
Section: Discussionmentioning
confidence: 62%
“…The critical role played by Lys16-Glu22 salt bridges in stabilizing the in-register antiparallel structures has been identified in previous experimental and theoretical studies. A combined spectroscopic and microscopy study has demonstrated that the weakening of this salt bridge interaction under acidic p H conditions results in other morphologies . In another experimental study, the introduction of an E22Q mutation on Aβ 16–22 resulted in a parallel structure of the final assembly .…”
Section: Discussionmentioning
confidence: 79%
“…This confirms the experimental observation that the propensity of PTH 25–37 to form amyloid is much lower than that of other peptides, such as that of Aβ 16–22 . For the latter, we observe the formation of ordered hexamers when simulated under the same conditions as here, while ThT experiments for this peptide show that fibrils are already present at the beginning of the measurements . For both PTH 25–37 and P4, we even see a decrease in interpeptide β-sheets when we increase the system size to the hexamer, which can be explained by the increase in dimensionality of the conformational space, which allows for more interpeptide interactions and makes it less likely to see ordered aggregates on short time scales.…”
Section: Resultsmentioning
confidence: 72%
“…In particular, the Aβ (16−22) peptide was shown to form fibrils within a time frame of 2 μs using variants of the CHARMM36m force field, whereas fibrils did not form successfully using AMBER99SBdisp. 22,64 In another study, the amphipathic (FKFE) 2 peptide was shown to form a fibril using the AMBER99SB-ildn force field, and at high peptide concentrations, increasing temperature was shown to accelerate this process. 21 In the same vein, simulations with a preformed fibril and a few peptides randomly located in the simulation box were used to study fibril growth 65−67 and secondary nucleation.…”
Section: ■ All-atom Simulationsmentioning
confidence: 99%